Testicular Torsion in the Absence of Severe Pain: Considerations for the Pediatric Surgeon - Alexander Kapp; David Troxler; Friederike Prüfer; Stefan Holland-Cunz; Martina Frech; Stephanie J. Gros (Children, 2021)
Testicular torsion is a surgical emergency. Early diagnosis and surgical treatment are vital in order to preserve the affected gonad. Current surgical teaching emphasizes sudden, severe, persistent, unilateral scrotal pain as a cardinal symptom of testicular torsion. We present the case of unilateral testicular torsion in a 14-year-old patient who presented with the absence of severe pain. Despite a delayed presentation to the emergency department, the gonad could be salvaged successfully. Literature on the topic of testicular torsion presenting with minimal pain is limited. Nevertheless, pediatric surgeons might be faced with cases similar to the one we describe. Underestimating this phenomenon might lead to a delay of treatment. In such cases, ultrasound can be a beneficial addition in the diagnosis and accelerate definitive operative treatment. The presented case clearly demonstrates that, although we do not include testicular torsion without severe pain in our surgical teaching algorithms, we might encounter it in our clinical practice.